Fresno's Historic Van Ness Avenue Entrance Sign - Watkins, Howard::::::::: (1984)
"FRESNO The Best Little City in the U.S.A. Van Ness Ave. Entrance" sign south of downtown area Howard's 1965 Dodge Dart parked; no other cars; railroad crossing arm upright